2011
DOI: 10.1186/1752-1505-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Uranium and other contaminants in hair from the parents of children with congenital anomalies in Fallujah, Iraq

Abstract: BackgroundRecent reports have drawn attention to increases in congenital birth anomalies and cancer in Fallujah Iraq blamed on teratogenic, genetic and genomic stress thought to result from depleted Uranium contamination following the battles in the town in 2004. Contamination of the parents of the children and of the environment by Uranium and other elements was investigated using Inductively Coupled Plasma Mass Spectrometry. Hair samples from 25 fathers and mothers of children diagnosed with congenital anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…In addition soil and water samples were analyzed. Results indicated that man-made slightly enriched uranium was present in soil and in the hair of the parents, with a trend of increasing concentration along the hair strands back to 2005 but that no other genotoxic elements were present which could explain the levels of cancer and congenital disease 4. The question of the incidence and types of congenital anomalies remains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition soil and water samples were analyzed. Results indicated that man-made slightly enriched uranium was present in soil and in the hair of the parents, with a trend of increasing concentration along the hair strands back to 2005 but that no other genotoxic elements were present which could explain the levels of cancer and congenital disease 4. The question of the incidence and types of congenital anomalies remains.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental aspect of the problem was studied in 2010 when hair sample analysis of 52 elements was carried out on the parents of children diagnosed with congenital anomalies 4. In addition soil and water samples were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Only the first case was included in that study. The presence of high concentrations of mercury and bismuth11 may suggest that environmental pollution from mercury, bismuth and perhaps other trace minerals is the cause of the high incidence and the strange presentations of anterior abdominal wall thickness defects in Fallujah patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the exposures at Aldermaston are only to Uranium and Plutonium particles, not to the other fallout residue radionuclides. Another piece of evidence is the high level of leukemia found in Fallujah Iraq where the radioactivity exposures were only to Uranium particles [37,38]. The question of the radiobiological effects of Uranium has been discussed recently [22,39].…”
Section: Discussionmentioning
confidence: 99%